Rawḍat al-munajjimīn - ʼl-Khayr, Shahmardān b. Abi (Miras Maktoob, ISBN: 9789004365452., 2020)
In the first centuries of Islam, Arabic gradually replaced Middle Persian to become the language of the new religion and the administration of Iran. Works in Middle Persian were translated into Arabic and Persian authors also started writing directly in Arabic. From the fifth/eleventh century onward, there arose a need for works in New Persian, either translated from Arabic or composed in New Persian straightaway. The work published in this volume is a product of that period. Not much is known about the life of its author, Shahmardān b. Abi ʼl-Khayr. A resident of Gurgān and Astarābād, he was a scholar who also worked as a secretary and financial officer. In astronomy, he was a student of Abu ʼl-Ḥasan Nasawī (fl. 2nd quart. 5th/11th cent.). Shahmardān's work is an accessible, popularized compilation of the works of others, among them Abū Maʿshar (d. 272/886), Kushyār b. Labbān (fl. late 4th/10th cent.), and Bīrūnī (d. 440/1048)